THE EFFECT OF SHORT MESSAGE SERVICE (SMS) TEXTING ON MEDICATION ADHERENCE AMONG TUBERCULOSIS PATIENTS - Prasetyo, Yunus Adhy (STIK Immanuel Bandung, 2019)
The study was conducted to examine the effect of Short Message Service (SMS) Texting on medication adherence among tuberculosis patients. 68 persons diagnosed with tuberculosis and registered in the public health center in Klari, Karawang, West Java, Indonesia, were randomly appointed to an experimental or control group; 34 persons assigned to each group. Participants in the experimental group received routine SMS Texting, while those in the control group receive none. Data were analyzed using Dependent t-test and Independent t-test. The results indicated that after participating by receiving SMS texting, there was a significant improvement in medication adherence in TB patients in the experimental group, which was shown by significant difference in mean score of medication adherence. In addition, after participating in the program, there was a meaningful difference in mean scores of medication adherence between the experimental group (X=6.38, SD=0.85) and the control group (X=3.64, SD=1.04), p<0.01. The SMS Texting method appears to be effective in improving medication adherence among TB patients.